Infusing innovation into organizations a systems engineering approach - Darrin, M. Ann Garrison; Krill, Jerry A. (CRC Press, 2016)
Infusing Innovation into Organizations: A Systems Engineering Approach introduces a systemic approach that supports an innovative culture and describes novel approaches to addressing problems using creative, viable solutions. This book serves undergraduate and graduate-level professors and students in systems engineering as well as managers and consultants working in systems analysis and design.